PENYULUHAN PEMERIKSAAN PAYUDARA SECARA KLINIS DENGAN PEMERIKSAAN RADIOLOGI DI DESA KARANGSUNO KABUPATEN KENDAL - Lucky Restyanti Wahyu Utami; Masfufatun Jamil (Jurnal Edukasi Pengabdian Masyarakat, 2026)
The lack of public knowledge regarding clinical breast examinations can affect the delay in early detection of breast disease in women. Therefore, the purpose of the community service activities given to mothers in Karangsuno Village, Cepiring District, Kendal Regency, Central Java Province is expected to contribute to increasing the level of understanding of breast disease in women, especially understanding related to the types of radiological examinations to establish an early diagnosis so that it can help reduce the number of disease incidents, especially in Kendal Regency. The community service activities were carried out using a lecture method. Based on the community service activities that have been carried out, it can be concluded that there is an increase in knowledge among participants regarding clinical breast examinations using radiological examinations by 69% and there is an increase in awareness among participants to perform clinical breast examinations using radiological examinations if they feel symptoms of breast pain by 77%.